On the Development of College Student Information Management System - Jin Anjiang (SHS Web of Conferences, 2015)
currently there exist severe fragmentation, different development standards, lack of sufficient support and other problems in the development of college student information management system. Therefore accelerating the development of student information management system is of necessity to improve universities’ management and administration efficiency. From the perspective of customers’ demands, the system should be designed and developed on the basis of Web Service by adopting B/S structure and SQL Server technology so as to coordinate applicability, security, compatibility, stability, maintainability and other non-functional demands.